正交试验法优化北极海洋沉积物中生源硅提取条件 - 陈精锋; 高爱国; 赵冬梅; 杨丽; 张延颇; 汪江萍 (2011)
生源硅主要来源于硅藻等生物,生源硅的积累反映上层水体中海洋生产力的时空变化,是古生产力和古气候研究的重要工具.为准确测定北极海洋沉积物中生源硅含量,优化生源硅化学提取法的提取条件,通过正交试验法,探讨了不同因素对生源硅提取效率的影响,优选出适合北极海洋沉积物中生源硅测定的实验条件.结果表明,各因素对提取效率的影响程度依次为:提取剂浓度>固液比>提取剂种类>提取温度;化学提取法的优选条件为:0.50 MOl/l氢氧化钠,固液比1.25 g/l,提取温度90℃.测得北极海洋沉积物标样中生源硅含量为57.03 Mg/g,平行误差2.51%,方法加标回收率介于76.15%--92.11%,相对标准偏差(rSd)为1.93%--7.52%. Biogenic silica(BSi) is a sort of amorphous silica from diatom,radiolarians,sponges and other siliceous organisms.BSi may reflect the spatial and temporal distribution of primary productivity and the environmental changes of aquatic systems.BSi has been widely used as a proxy of paleoceanography events and paleoclimate.In order to determinate the content of biogenic silica accurately from the sediment in the Arctic Ocean,this study used orthogonal experiment,tried to explore the influence of various factors on the determination of BSi,and then to optimize the experimental conditions.The results of orthogonal experiment show that the influence of each factor from high degree to low degree is as follows:solvent concentration > solid to liquid ratio > extraction solvents> extraction temperature.The optimized condition for the chemical extraction is suggested to be:the concentration of extraction solvent sodium hydroxide is 0.50 mol/L,the ratio of solid to liquid is 1.25 g/L and the extraction temperature is 90 ℃.The BSi content in the Arctic Ocean sediments is calculated as 57.03 mg/g(parallel error 2.51%),the ration of sample added recovery is between 76.15% and 92.11%,and the relative standard deviation is between 1.93% and 7.52%. 国家自然科学基金项目(40376017;40576060)